SMA-Coated Aluminum Structural Elements with Enhanced-Thermo-Mechanical Performance. Issue 4 (July 2018) - Exarchos, D.A.; Dalla, P.T.; Tragazikis, I.K.; Dassios, K.G.; De Crescenzo, C.; Karatza, D.; Musmarra, D.; Chianese, S.; Matikas, T.E.
This work presents the development of novel multifunctional Shape Memory Alloy (SMA) coatings aiming to improve the mechanical behavior of structural components, as well as their corrosion resistance. The groundbreaking concept of the new coating material is described briefly as follows: Upon heating, the SMA coating tends to recover its experienced deformation and return to its original shape. At that point, shear forces developing at the interface between coating and structure are expected to mitigate the deformation of the structure and reduce its overall stress field level. The latter is a great benefit for regions where cracks exist, since the local reduction of the stress field will delay the crack propagation and hence the structural failure. Numerical analysis is performed to gain understanding of the expected thermomechanical response of the entire SMA-coated composite structure. The influence of the alloy composition and precipitates on the thermomechanical properties are also examined. The SMA coating is subjected to appropriate processing conditions and deposited on metallic substrates of proper geometry following a custom-designed two-phase process, which enables beneficial shape recovery enabling the efficient mitigation of the structure's deformation. Processing consists of aging heat treatments, which are of paramount importance for endowing the coating with the shape memory effect. The effect of heat treatment conditions on the thermo-mechanical fatigue response of the material was also characterized. The developed SMA coatings on aluminum structural elements can find significant application in aeronautical engineering, as for example in the aircraft wing box structure reinforcement and the fuselage structure to enhance their structural integrity.